1982
DOI: 10.1002/jcb.240200304
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of growth factors in human cartilage

Abstract: Growth factor activity has been identified in the chondrocytes and extracellular matrix (ECM) fractions of human costal cartilage. There was about five times more growth factor activity in the ECM than was found to be associated with the chondrocytes. The growth factor activity in chondrocytes was found to be associated with chromatin. Both the chromatin-associated growth factor (CAGF) activity and extracellular matrix growth factor (EMGF) activity were characterized for molecular weight, charge, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In this respect, it was of interest to determine whether TGF-P can also influence the proliferation of articular chondrocytes. So far, the factors that regulate this proliferative activity have not been defined, although several local autocrine or paracrine growth factors have been discovered in cartilage (Beckoff and Klagsbrun, 1982;Kato et al, 1983). To test the hypothesis that TGF-P can regulate chondrocyte growth in vitro, we studied its effects on the proliferation rate of cultured rabbit articular chondrocytes and compared them to the action of epidermal growth factor (EGF) as a nontransforming and typical growth factor.…”
mentioning
confidence: 99%
“…In this respect, it was of interest to determine whether TGF-P can also influence the proliferation of articular chondrocytes. So far, the factors that regulate this proliferative activity have not been defined, although several local autocrine or paracrine growth factors have been discovered in cartilage (Beckoff and Klagsbrun, 1982;Kato et al, 1983). To test the hypothesis that TGF-P can regulate chondrocyte growth in vitro, we studied its effects on the proliferation rate of cultured rabbit articular chondrocytes and compared them to the action of epidermal growth factor (EGF) as a nontransforming and typical growth factor.…”
mentioning
confidence: 99%
“…This is likely to contribute to an autocrine/paracrine .control of chondrocyte mitogenesis since cells expressed abundant mRNA encoding one of the high affinity FGF receptors, fZg (Lee et al, 1989), and the basal DNA synthetic rate of the cells was significantly reduced by the biological neutralization of the released basic FGF with a specific blocking antibody. The presence of a cationic growth factor with isoelectric point between 9 and 10, and molecular weight approximately 17 kDa was previously recorded within bovine articular and human costal cartilage by Azizkhan and Klagsbrun (1980) and Bekoff and Klagsbrun (1982). These studies were confirmed and the isolated peptide called 'cartilage-derived growth factor' (Sullivan and Klagsbrun, 1985) which was subsequently shown to be identical to basic FGF with a PI of 9.8 and a molecular weight of 18 kDa (Lobb et al, 1986;Too et al, 1987; Gospodarow- icz , 1989).…”
Section: Discussionmentioning
confidence: 99%